2016
DOI: 10.1128/jvi.02376-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Herpes Simplex Virus 1 (HSV-1) Chimera in Which the Us3 Protein Kinase Gene Is Replaced with the HSV-2 Us3 Gene

Abstract: Us3 protein kinases encoded by herpes simplex virus 1 (HSV-1) and 2 (HSV-2) play important roles in viral replication and pathogenicity. To investigate type-specific differences between HSV-1 Us3 and HSV-2 Us3 in cells infected by viruses with all the same viral gene products except for their Us3 kinases, we constructed and characterized a recombinant HSV-1 in which its Us3 gene was replaced with the HSV-2 Us3 gene. Replacement of HSV-1 Us3 with HSV-2 Us3 had no apparent effect on viral growth in cell cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
2
12
0
Order By: Relevance
“…These membranous invagination structures were present at a lower but consistent frequency in HaCaT cells infected with wild-type HSV-1(F), YK633 (UL51-S184A/D-repair), or YK639 (ΔUL51-repair) ( Fig. 7), as reported previously (45). The quantification of virus particles at different morphogenetic stages showed that 24.4% and 27.8% of enveloped virions in HaCaT cells infected with YK631 (UL51-S184A) or YK638 (ΔUL51), respectively, were present in the perinuclear space and invagination structures.…”
Section: Effect Of Phosphorylation Of the Identified Phosphorylation supporting
confidence: 87%
See 2 more Smart Citations
“…These membranous invagination structures were present at a lower but consistent frequency in HaCaT cells infected with wild-type HSV-1(F), YK633 (UL51-S184A/D-repair), or YK639 (ΔUL51-repair) ( Fig. 7), as reported previously (45). The quantification of virus particles at different morphogenetic stages showed that 24.4% and 27.8% of enveloped virions in HaCaT cells infected with YK631 (UL51-S184A) or YK638 (ΔUL51), respectively, were present in the perinuclear space and invagination structures.…”
Section: Effect Of Phosphorylation Of the Identified Phosphorylation supporting
confidence: 87%
“…Although the UL34 and UL31 proteins were colocalized along the nuclear rim in the majority of HaCaT cells infected with wild-type HSV-1(F), YK633 (UL51-S184A/D-repair), or YK639 (ΔUL51-repair) (69.9% to 77.2%), some UL34 and UL31 proteins were colocalized in punctate structures adjacent to the nuclear rim (22.8% to 30.1%) ( Fig. 9), as reported previously (45). In contrast, in HaCaT cells infected with YK631 (UL51-S184A) or YK638 (ΔUL51), UL31 and UL34 were colocalized in punctate structures adjacent to the nuclear rim in the majority of cells (76.2% or 80.5%, respectively) and were colocalized along the nuclear rim in a smaller percentage of cells (Fig.…”
Section: Effect Of Phosphorylation Of the Identified Phosphorylation supporting
confidence: 85%
See 1 more Smart Citation
“…By contrast, the strains utilized by Morimoto and colleagues express catalytically inactive forms of pUs3 raising the possibility that pUs3 is important for HSV-2 nuclear egress, but its kinase activity is not (29). Interestingly, replacement of HSV-1 Us3 with HSV-2 Us3 resulted in a chimeric strain that displayed nuclear egress deficiencies (32). These findings indicated that HSV-2 Us3 could not complement the loss of HSV-1 Us3 and further supported the idea that HSV-2 pUs3 does not function in nuclear egress.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, it has been reported that HSV-1 Us3 and HSV-2 Us3 differ in their contributions to viral neuroinvasiveness in mice (26,58). Recently, it has been reported that the replacement of HSV-1 Us3 with HSV-2 Us3 compensated for the phosphorylation of HSV-1 gB Thr-887, which is not conserved in HSV-2 gB, leading to the effect of its phosphorylation and the downregulation of the cell surface expression of gB in infected cells (59). These observations suggest that phosphorylation sites in viral proteins may have evolved to enable viral kinases to acquire new functions in viral protein regulation.…”
Section: Discussionmentioning
confidence: 99%